ASSESSMENT FOR LEARNING: DEFINITION, PURPOSE, DISTINCTIVE FEATURES - Tashpulatova , Nafisa Baxtiyarovna (Innovative Development in Educational Activities, 2024)
In this article, an emphasis has been put on defining formative assessment and elaborate readers’ understanding of the term. The author highlights the central role of formative assessment to motivate language learners in the teaching and learning process.